Implementation of dosimetry equipment and phantoms at the MedAustron light ion beam therapy facility. Issue 1 (23rd November 2017) - Grevillot, Loïc; Stock, Markus; Palmans, Hugo; Osorio Moreno, Jhonnatan; Letellier, Virgile; Dreindl, Ralf; Elia, Alessio; Fuchs, Hermann; Carlino, Antonio; Vatnitsky, Stanislav
Abstract : Purpose: To describe the implementation of dosimetry equipment and phantoms into clinical practice of light ion beam therapy facilities. This work covers not only standard dosimetry equipment such as computerized water scanners, films, 2D‐array, thimble, and plane parallel ionization chambers, but also dosimetry equipment specifically devoted to the pencil beam scanning delivery technique such as water columns, scintillating screens or multilayer ionization chambers. Method: Advanced acceptance testing procedures developed at MedAustron and complementary to the standard acceptance procedures proposed by the manufacturer are presented. Detailed commissioning plans have been implemented for each piece of dosimetry equipment and include an estimate of the overall uncertainty budget for the range of clinical use of each device. Some standard dosimetry equipment used in many facilities was evaluated in detail: for instance, the recombination of a 2D‐array or the potential use of a microdiamond detector to measure reference transverse dose profiles in water in the core of the primary pencil beams and in the low‐dose nuclear halo (over four orders of magnitude in dose). Results: The implementation of dosimetry equipment as described in this work allowed determining absolute spot sizes and spot positions with an uncertainty better than 0.3 mm. Absolute ranges are determined with an uncertainty comprised of 0.2–0.6 mm, depending on the measured range and were reproduced with a maximum difference of 0.3 mm over a period of 12 months using three different devices. Conclusion: The detailed evaluation procedures of dosimetry equipment and phantoms proposed in this work could serve as a guidance for other medical physicists in ion beam therapy facilities and also in conventional radiation therapy.